2020
DOI: 10.3390/brainsci10121011
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical and Behavioral Characterization after Acute and Repeated Exposure to Novel Synthetic Cannabinoid Agonist 5-MDMB-PICA

Abstract: Since the early 2000s, herbal mixtures containing synthetic cannabinoids (SCs), broadly known as Spice/K2, have been marketed as a legal marijuana surrogate and have become very popular among adolescents. Adolescence is a critical period of development, which is associated with an increased vulnerability to the central effects of drugs. Despite growing concerns about the negative effects of the use of SCs, newly synthetized compounds are increasingly detected in drugs seized by the authorities, posing a seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Moreover, in the present study, we reported that adolescent exposure to JWH-018 by IVSA induces repetitive/compulsive-like behaviors at adulthood, as revealed by the increase of repetitive/compulsive-like phenotypes both in the nestlet shredding and marble burying tests. Consistent with the present observations, adolescent mice treated with the SCRA 5F-MDMB-PICA for 14 consecutive days displayed repetitive/compulsive-like states at adulthood, as indexed by heightened perseverative responses in the marble burying test (Musa et al 2020 ). Accordingly, Murphy et al ( 2017 ) demonstrated that chronic administration of THC during adolescence increased nestlet shredding during adulthood; however, adolescence animals showed a trend to statistical significance in burying marbles only immediately after THC treatment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, in the present study, we reported that adolescent exposure to JWH-018 by IVSA induces repetitive/compulsive-like behaviors at adulthood, as revealed by the increase of repetitive/compulsive-like phenotypes both in the nestlet shredding and marble burying tests. Consistent with the present observations, adolescent mice treated with the SCRA 5F-MDMB-PICA for 14 consecutive days displayed repetitive/compulsive-like states at adulthood, as indexed by heightened perseverative responses in the marble burying test (Musa et al 2020 ). Accordingly, Murphy et al ( 2017 ) demonstrated that chronic administration of THC during adolescence increased nestlet shredding during adulthood; however, adolescence animals showed a trend to statistical significance in burying marbles only immediately after THC treatment.…”
Section: Discussionsupporting
confidence: 92%
“…The first key finding revealed by our investigation is that adolescent male mice (i) acquired operant behavior (lever pressing) for JWH-018 with an inverted U-shaped dose–response curve; (ii) that this behavior was specifically directed at obtaining JWH-018 since it increased under a Progressive Ratio schedule of reinforcement, and was absent in vehicle mice; (iii) that JWH-018 IVSA was reduced by pretreatment of the CB1-antagonist/inverse agonist AM251. Specifically, results showed that CD1 adolescent mice acquired JWH-018 IVSA at the dose of 7.5 µg/kg/inf (Fixed Ratio 1–3), displaying higher sensitivity to this agent compared to that shown by C57BL/6 (C57) adult mice (De Luca et al 2015 ), thereby confirming the reinforcing effects of SCRAs identified in Spice/K2 products (De Luca et al 2016 ; Musa et al 2020 ). Of note is that we established a self-administration protocol for JWH-018 using a less sensitive strain of mice, which implies greater reinforcing properties of this particular SCRA with respect to those of previous generations (Martellotta et al 1998 ; Navarro et al 2001 ), and with respect to THC (Tanda and Goldberg 2003 ; Justinova et al 2005 ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The effects on neuronal development have been also studied. Brain malformations have also been shown due to inhibition of Pax-6, which is necessary for the closure of the nascent neural tube, as well as CB 1 -mediated ocular malformation, lack of memory retention and hyperactivity, and inhibition of new synapses formation in hippocampal neurons [ 68 ]. Moreover, SCRAs induced hyperreflexia and myoclonias, not induced by THC, with effects prevented by the administration of CB 1 receptor antagonist/reverse agonist AM 251, while this is not the case for sensory-motor impairments [ 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Memory impairment at the Morris water maze was also described in adult mice treated with WIN55212.2 during adolescence ( 37 ). Musa et al reported a higher anxiety-like and compulsive-like state in adulthood after a 5F-MDMB-PICA exposure during adolescence ( 39 ).…”
Section: Discussionmentioning
confidence: 99%